Evaluation of Wear and Hardness Properties of 3D-Printed Polylactide/Hydroxyapatite/Titania Composites - Olam, Mikail; Tosun, Nihat (Wiley, 2025)
Polylactic acid (PLA), which shows promise as a replacement for non-biobased polymers, has limitations in many applications due to poor mechanical properties. Recently, PLA-based composite filaments have been developed to address this issue. In this study, composite filaments made of polylactic acid (PLA) containing titanium dioxide (titania, TiO2), synthetic hydroxyapatite (HA), and natural hydroxyapatite (NHA) were developed for biomedical applications. These composite filaments were used to easily 3D print objects on a fused deposition modeling (FDM) printer. In the analysis of the samples using EDX, it was observed that the filaments maintained the specified mixing ratios. The Mapping analysis indicated that the elements in the PLA/HA/NHA/TiO2 mixtures were evenly distributed. The maximum load (468 N) and displacement (1.546 mm) occurred in the PLA composite with 1% HA and 4% TiO2. The composite with the lowest wear was the one with 98% PLA, 1% HA, and 1% TiO2, while the composite with the highest wear was the one with 95% PLA, 1% HA, and 4% TiO2. The composite with the highest average friction coefficient was the one with 98% PLA, 1% NHA, and 1% TiO2. The lowest Shore D hardness value was 71.4 in the material containing 98% PLA, 1% NHA, and 1% TiO2, and the highest value was 80.3 in the composite of 95% PLA, 1% HA, and 4% TiO2.
Keywords: hardness; hydroxyapatite; polylactide; titania; wear